How language evolved as a backchannel between two feedback loops - von Heiseler, Till Nikolaus (Theoria et Historia Scientiarum, 2015)
Language is what makes us human. It is the basis of human knowledge, culture, and society. Despite its importance, how language evolved is still a mystery. Various recent studies suggest that humans developed through a "super-fast" evolutionary process found nowhere else within the animal kingdom. This suggests a discontinuity in the evolutionary process itself. We propose the following model: Humans evolved in a unique evolutionary system consisting of two feedback loops, there being a backchannel between them; the lower loop producing the variations needed for selection in the upper loop to take place. What is meant by the "backchannel" here is a structure enabling the selection of the lower loop to "anticipate" the selection of the upper one. The content of this backchannel is displaced action encoded in narration. We show that not only the human brain and language but also most of the unique human faculties (including theory of mind, episodic memory and the unique human altruism) are adapted almost exclusively to developing the functioning of the backchannel (narration) at a super-fast evolutionary pace.